Creation of single molecular conjugates of metal–organic cages and DNA. Issue 33 (5th April 2023) - Nakajo, Toshinobu; Kusaka, Shinpei; Hiraoka, Haruka; Nomura, Kohei; Matsubara, Noriaki; Baba, Rintaro; Yoshida, Yuki; Nakamoto, Kosuke; Honma, Masakazu; Iguchi, Hiroaki; Uchihashi, Takayuki; Abe, Hiroshi; et al.
Abstract : We report the development of an equimolar conjugate of a metal– organic cage (MOC) and DNA (MOC-DNA ) for the first time. The unique functions derived from the conjugation are also reported. Abstract : Here we report the development of an equimolar conjugate of a metal– organic cage (MOC) and DNA (MOC-DNA ). Several MOC-DNA conjugates were assembled into a programmed structure by coordinating with a template DNA having a complementary base sequence. Moreover, conjugation with the MOC drastically enhanced the permeability of DNA through the lipid bilayer, presenting great potential as a drug delivery system.